KONSEP KEADILAN DALAM HUKUM BISNIS ISLAM: STUDI ATAS AKAD DAN TRANSAKSI MODERN - Anggi Anggreini; Aina Fitri Alma; Fathimah Fathimah (Media Riset Bisnis Manajemen Akuntansi, 2025)
Justice is a core value in Islamic teachings and serves as the foundational principle in Islamic business law. This study examines the concept of justice in Islamic business law, specifically within the context of modern contracts and transactions. Using a qualitative approach with normative and descriptive methods, the research classical Islamic legal principles and their application to contemporary practices such as smart contracts, cryptocurrency, and digital crowdfunding. Findings reveal that justice in Islamic business is not merely a moral imperative but an operational standard to ensure fairness, transparency, and balance in transactions. The study highlights the need for reinterpretation through contemporary ijtihad to address legal issues emerging from economic digitalization while remaining aligned with shariah. Additionally, the research underscores the role of regulators and Islamic financial institutions in promoting equitable business practices. Enhanced legal awareness and ethical literacy among Muslim entrepreneurs are also emphasized as key to ensuring just practices in the evolving business landscape. This study contributes to the dynamic understanding of Islamic law as a relevant legal system capable of responding to modern challenges without compromising its core values.Keywords : contract, digital transaction, Islamic business law, justice, shariah.